Determinants of first trimester combined test participation within the central region of the Netherlands. (May 2015) - Crombag, Neeltje M. T. H.; Schielen, Peter C. J. I.; Hukkelhoven, Chantal W.; Iedema, Rita; Bensing, Jozien M.; Visser, Gerard H. A.; Stoutenbeek, Philip; Koster, Maria P. H.
Abstract Objective Our objective is to study the association between potentially influential determinants and first‐trimester combined test (FCT) uptake rates in the central region of the Netherlands. Methods Data were extracted from the national prenatal screening database Peridos and the Netherlands Perinatal Registry and compared at the level of the health care provider. Univariable and multivariable linear regression analysis was used to determine the effect of determinants (maternal age, parity, socio‐economic status (SES), mode of conception, ethnicity and urbanisation) on uptake. Results Prenatal screening data were available for 24 657 women and overall uptake rate was 25.7%. The strongest association with FCT uptake was found for advanced maternal age (β 2.2; 95% CI [1.7, 2.8]). Grand multiparity had a significantly negative association with FCT uptake (β −4.3; 95% CI [−5.9, −2.7]). Positive associations were found for very high urbanisation (β 0.3; 95% CI [0.1, 0.4]) and high SES (β 0.2; 95% CI [0.0, 0.3]). Conclusion Advanced maternal age is strongly associated with participation in prenatal testing. The role of age related risk perception should be incorporated in future policy making to support women in informed and autonomous decision making. The negative association of grand multiparity and FCT might be religion based but requires further research. © 2015 John Wiley & Sons, Ltd.